2021
DOI: 10.1111/jcpt.13385
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of hypoxia‐inducible factor prolyl hydroxylase inhibitors in anaemia of chronic kidney disease: A meta‐analysis including 13,146 patients

Abstract: What is known and objective Previous studies based on small‐sample clinical data proved that short‐term use of hypoxia‐inducible factor prolyl hydroxylase (HIF‐PHD) inhibitors increased haemoglobin levels in anaemic patients with chronic kidney disease (CKD). However, these studies reached conflicting conclusions on iron parameters and adverse event profiles. Our meta‐analysis aimed to evaluate the long‐term efficacy and safety of HIF‐PHD inhibitors in renal anaemia. Methods Randomized controlled trials compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 40 publications
2
67
0
Order By: Relevance
“…Another new promising therapy strategy is the inhibition of prolyl hydroxylase, which stabilizes hypoxia-inducible factor thus promoting erythropoietin production, increasing intestinal iron uptake and mobilization of iron stores [319]. Oral hypoxia-inducible factor prolyl hydroxylase inhibitors (HIF-PHI) including roxadustat, vadadustat, desidustat, daprodustat and molidustat were shown to significantly increase hemoglobin levels and total iron binding capacity concomitant to an decrease in hepcidin and ferritin levels in patients with anemia and chronic kidney disease [320]. Moreover, several preclinical studies have suggested a potential cardiovascular benefit due to direct actions of HIF activation in myocardial infarction, cardiac remodeling and atherosclerosis as well as amelioration of glucose and lipid metabolism [321].…”
Section: Stabilization Of Hypoxia-inducible Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Another new promising therapy strategy is the inhibition of prolyl hydroxylase, which stabilizes hypoxia-inducible factor thus promoting erythropoietin production, increasing intestinal iron uptake and mobilization of iron stores [319]. Oral hypoxia-inducible factor prolyl hydroxylase inhibitors (HIF-PHI) including roxadustat, vadadustat, desidustat, daprodustat and molidustat were shown to significantly increase hemoglobin levels and total iron binding capacity concomitant to an decrease in hepcidin and ferritin levels in patients with anemia and chronic kidney disease [320]. Moreover, several preclinical studies have suggested a potential cardiovascular benefit due to direct actions of HIF activation in myocardial infarction, cardiac remodeling and atherosclerosis as well as amelioration of glucose and lipid metabolism [321].…”
Section: Stabilization Of Hypoxia-inducible Factormentioning
confidence: 99%
“…In a recent meta-analysis by Chen and coworkers including 13,146 patients, HIF-PHI were well tolerated during long-term use with comparable risk of serious adverse events compared to patients treated only with ESAs. However, HIF-PHI treatment was associated with a slightly increased risk for thrombosis events when compared to patients treated only with ESAs [320]. Several phase 3 trials further evaluating the efficacy and safety of HIF-PHI in CKD patients including the long-term cardiovascular risk are currently ongoing.…”
Section: Stabilization Of Hypoxia-inducible Factormentioning
confidence: 99%
“…Several HIFs stabilisers are being developed, some of which have entered/finished phase 3 of clinical trials, including Vadadustat, Daprodustat and Roxadustat [ 273 ]. Meta-analyses of several randomised controlled trials showed that PHD inhibitors increase the levels of hemoglobin, serum transferrin and increase intestinal iron absorption while reducing levels of hepcidin in anaemic CKD patients [ 273 , 274 , 275 ]. These effects seem to be independent of inflammation [ 273 ].…”
Section: Novel Therapeutic Options For Targeting Iron Metabolismmentioning
confidence: 99%
“…HIF-PH inhibitors have rather peculiar complications; therefore, caution is warranted. In the clinical trials of HIF-PH inhibitor use for renal anaemia, it has been reported that the incidence of thromboembolism is higher than that of the control group [ 12 ]. Since the patient in our case report had ET, which is already associated with an increased risk of thrombosis [ 13 ], platelet count control and low-dose aspirin therapy were initiated; thus, thrombosis did not occur.…”
Section: Discussion/conclusionmentioning
confidence: 99%